PENGARUH KINERJA PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Heni Subekti; Risma Musfiyana; Sri Kawuri (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
The value of the company is an important thing that investors consider before they invest. The value of the company can provide maximum shareholder prosperity if the share price increases. The higher the stock price of a company, the higher the prosperity of shareholders. This study aims to determine the effect of liquidity (Current Ratio), profitability (ROE) and leverage (DER) on firm value (PBV) and determine whether dividend policy (Dividend Payout Ratio) can be used as an intervening variable on the liquidity relationship (Current Ratio), profitability (ROE) and leverage (DER) on firm value. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample in this study was taken using a purposive sampling technique, totaling 12 companies. The data analysis method used is descriptive analysis and data analysis using multiple linear regression method using SPSS software. The results show that liquidity (Current Ratio) has an effect on dividend policy, while profitability and leverage have no effect on dividend policy. Liquidity (Current Ratio) and leverage (DER) have no effect on the value of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. On the other hand, profitability and dividend policy have a significant and significant impact on the value of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. Meanwhile, the dividend policy is able to mediate the relationship between liquidity (Current Ratio) and the value of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. Likewise, the relationship between leverage (DER) and the value of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019 can be mediated by dividend policy. On the other hand, dividend policy cannot mediate the relationship between profitability and firm value.